Currency wars : the making of the next global crisis - Rickards, James (New York : Portfolio/Penguin, 2011)
Drawing on a mix of economic history, network science, and sociology, "Currency Wars" provides a rich understanding of the increasing threats to U.S. national security, from dollar devaluation to collapse in the European periphery, failed states in Africa, Chinese neomercantilism, Russian adventurism, and the current scramble for gold.
Prewar -- Financial war -- Reflections on a golden age -- Currency war I (1921-1936) -- Currency war II (1967-1987) -- Currency war III (2010- ) -- The G20 solution -- Globalization and state capital -- The misuse of economics -- Currencies, capital and complexity -- Endgame : paper, gold or chaos?
Includes bibliographical references (p. 263-280) and index.
Keywords: Currency crises; Foreign exchange; Financial crises